2014
DOI: 10.1016/j.atherosclerosis.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat composition and cardiac events in patients with type 2 diabetes

Abstract: In patients with type 2 diabetes without ischemic heart disease, a high intake of polyunsaturated fatty acids, especially alpha linolenic acid, was protective for the development of cardiac events..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In a prospective cohort analysis of 227 patients with type 2 diabetes, dos Santos et al (33) found that dietary PUFA intake >9.0% of total energy was associated with an up to 70% risk reduction for cardiac events. The protective role of PUFAs was especially significant for ALA, with the highest intake of ALA (highest quartile: >1.25% of energy) being associated with a 42% reduction in risk of cardiac events.…”
Section: Unsaturated Fasmentioning
confidence: 98%
“…In a prospective cohort analysis of 227 patients with type 2 diabetes, dos Santos et al (33) found that dietary PUFA intake >9.0% of total energy was associated with an up to 70% risk reduction for cardiac events. The protective role of PUFAs was especially significant for ALA, with the highest intake of ALA (highest quartile: >1.25% of energy) being associated with a 42% reduction in risk of cardiac events.…”
Section: Unsaturated Fasmentioning
confidence: 98%
“…Another possible reason is differences in the baseline dietary n-3 PUFA intake among the populations. In fact, in the present study, the mean EPA and DHA intake was low because less than 15% of our population consumes marine foods [ 27 ]. Thus, the main source of PUFA in the present study population was derived from vegetable oils, especially soybean oil.…”
Section: Discussionmentioning
confidence: 87%
“…However, the ALA itself could have beneficial effects, such as, anti-inflammatory properties that may be the link between this FA and the cardiometabolic risk [ 25 , 26 ]. In fact, in a recent cohort study of patients with type 2 diabetes without ischemic heart disease, a high intake of PUFA, especially ALA, was protective for the development of cardiac events [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that unsaturated fatty acids play important roles in membrane fluidity, and as mediators of signal transduction, cellular differentiation, and metabolic homeostasis . Increased MUFA, n ‐3 PUFAs, and an n ‐3/ n ‐6 ratio have been found related to the prevention of cardiovascular events . This increase in the content of unsaturated fatty acids was even found in the heart of male offspring from control rats fed the olive oil enriched diet, although not in the female group fed the same diet, and the putative transgenerational, dietary‐ and sex‐dependent mechanisms involved will require further research.…”
Section: Discussionmentioning
confidence: 98%